ACUTE EPIGLOTTITIS IN A BOY 3 YEARS - O. I. Lekomtseva; T. A. Britkova; N. A. Kravtsova; E. V. Pchelina; I. V. Ivanov (LLC "Diagnostics and Vaccines", 2016)
Аarticle describes the case of epiglottitis in a boy 3 years old, who was hospitalized  in a children's infectious disease department of city hospital of Izhevsk. He was hospitalized  in the department with a diagnosis of acute laryngotracheitis constrictive.The diagnosis  was clarified following an anesthetized laryngoscopy.